The continuing debate of 5-alpha reductase inhibitors and prostate cancer risk - Faisal, Farzana A.; Tosoian, Jeffrey J. (Translational Cancer Research, 2018)
Finasteride and dutasteride are 5-alpha reductase inhibitors (5-ARIs) which have been shown to improve symptoms of benign prostatic hyperplasia (BPH) and reduce the risk of urinary retention and BPH-related surgeries (1,2). These medications inhibit the conversion of testosterone to the more potent androgen dihydrotestosterone. Given that androgens are known to influence the development of prostate cancer (PCa), it was proposed that 5-ARIs could additionally serve as chemoprotective agents and reduce the prevalence of PCa in the general population (3).